2015
DOI: 10.1007/s00228-015-1866-3
|View full text |Cite
|
Sign up to set email alerts
|

The use of melatonin in Swedish children and adolescents—a register-based study according to age, gender, and medication of ADHD

Abstract: More Swedish boys than girls used melatonin regularly. The boys started treatment earlier and more often combined regular use of melatonin with regular use of medication for ADHD. This indicates that girls and boys partly are prescribed melatonin for different reasons. About half of the younger children stayed on melatonin treatment for several years, while 90% of adolescents (15-19 years) concluded their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
(19 reference statements)
5
13
0
Order By: Relevance
“…The increasing prevalence and incidence of dispensation of melatonin prescriptions in children in our study has previously been shown in other Nordic European countries [11][12][13]27]. A Norwegian study showed an increase in prevalence for girls 1.5-7.7 per 1000 and boys 3.4-11.0 per 1000 during the time period 2004-2012 [11].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The increasing prevalence and incidence of dispensation of melatonin prescriptions in children in our study has previously been shown in other Nordic European countries [11][12][13]27]. A Norwegian study showed an increase in prevalence for girls 1.5-7.7 per 1000 and boys 3.4-11.0 per 1000 during the time period 2004-2012 [11].…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, a Danish study showed that the number of melatonin prescriptions (all off-label) increased expansively from 2006 to 2012 [13]. Another Swedish study investigating melatonin use among children and adolescents 0-19 years of age between 2006 and 2013 reported similar results [12]. Furthermore, the Swedish study stressed the importance of continuous follow-up of melatonin use in a pediatric population.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…A long-term follow-up study by Hoebert et al (2009) in 94 children with ADHD and sleeponset insomnia indicated that melatonin discontinuation was associated with relapse of sleep-onset insomnia in 92% of cases. A register study in Sweden indicates that 50% of children prescribed melatonin were also using ADHD medications and that melatonin usage was higher in boys than girls (Furster and Hallerbäck 2015). There is little comprehensive evidence for other chronotherapeutic approaches in ADHD.…”
Section: Intervention Studiesmentioning
confidence: 99%